Interview and focus group data on intergenerational resilience in Aklavik, NWT, 2009 - Cindy Dickson, Council Of Yukon First Nations; Andrea Rawluk, Department Of Resource Economics; Brenda Parlee, Department Of Resource Economics; Ehdiitat Renewable Resource Council; Gwich'in Council International (Canadian Cryospheric Information Network, 2016)
The data consists of quantitative and qualitative data. 26 interviews semi-structured interviews using an interview guide to collect quantitative and qualitative data were done with elders (n=9), adults (n=8) and youth (n=9). 2 focus groups were done with youth (n=6) and elders (n=6). There are audio files and transcriptions for all interviews. 7 unstructured interviews were done with elders (n=5) and youth (n=2) to collect qualitative data : Purpose: Conduct case study research on resilience. The intention for the project was to understand how communities are ensuring their health and wellbeing in the face of social and ecological changes. The aim of the research was to understand how resilience was defined in Gwich'in and Inuvialuit cultures; explore pre-existing variables as measures to resilience with youth, adults, and elders; and learn what changes in the community and on the land different generations consider to be negative and positive for them. : Summary: Not Applicable